Post-transcriptional markers associated with clinical complications in Type 1 and Type 2 diabetes mellitus. (15th June 2019) - Massaro, Juliana Doblas; Polli, Claudia Danella; Costa e Silva, Matheus; Alves, Cinthia Caroline; Passos, Geraldo Aleixo; Sakamoto-Hojo, Elza Tiemi; Rodrigues de Holanda Miranda, Wallace; Bispo Cezar, Nathalia Joanne; Rassi, Diane Meyre; Crispim, Felipe; Dib, Sergio Atala; Foss-Freitas, Maria Cristina; et al.
Abstract: The delayed diagnosis and the inadequate treatment of diabetes increase the risk of chronic complications. The study of regulatory molecules such as miRNAs can provide expression profiles of diabetes and diabetes complications. We evaluated the mononuclear cell miRNA profiles of 63 Type 1 and Type 2 diabetes patients presenting or not microvascular complications, and 40 healthy controls, using massive parallel sequencing. Gene targets, enriched pathways, dendograms and miRNA-mRNA networks were performed for the differentially expressed miRNAs. Six more relevant miRNAs were validated by RT-qPCR and data mining analysis. MiRNAs associated with specific complications included: i) neuropathy (miR-873-5p, miR-125a-5p, miR-145-3p and miR-99b-5p); ii) nephropathy (miR-1249-3p, miR-193a-5p, miR-409-5p, miR-1271-5p, miR-501-3p, miR-148b-3p and miR-9-5p); and iii) retinopathy (miR-143-3p, miR-1271-5p, miR-409-5p and miR-199a-5p). These miRNAs mainly targeted gene families and specific genes associated with advanced glycation end products and their receptors. Sets of miRNAs were also defined as potential targets for diabetes/diabetes complication pathogenesis. Highlights: MiRNAs have been associated with diabetes pathogenesis, clinical features and complications. Massive parallel sequencing may identify miRNAs in diabetes patients exhibiting or not complications. Sets of differentially expressed miRNAs were associated with Type 1/2 diabetes complications. Modulated miRNAs mainly targeted genes associated with advanced glycation end products and their receptors. MiRNA identification may discriminate patients exhibiting risk for diabetes complications.